Diagnostic accuracy of point-of-care devices for detection of anemia in community settings in India - Sutapa Bandyopadhyay Neogi; Jyoti Sharma; Shivam Pandey; Nausheen Zaidi; Maitreyee Bhattacharya; Rakhee Kar; Sitanshu Sekhar Kar; Abhishek Purohit; Sanjib Bandyopadhyay; Renu Saxena (BMC, 2020)
Abstract Background Accurate diagnosis of anemia by community workers using a point-of-care device is a challenge. The objective of the study was to establish the diagnostic accuracy of point-of-care devices for detecting anemia in community settings. Methods It was diagnostic accuracy study with cross-sectional design on adult patients attending the outpatient department of rural/ urban health centres of Medical colleges from India. The index tests were HemoCue, TrueHb, Massimo's device and spectroscopic device, compared against autoanalyzer (gold standard). Accuracy was expressed by sensitivity, specificity, likelihood ratios, predictive values, area under the curve (AUC) and levels of agreement. For the diagnostic accuracy component, 1407 participants were recruited with a minimum of 600 for each device. An additional 200 participants were considered to elucidate the performance of devices in different weather conditions. Results HemoCue and TrueHb performed better than Massimo and spectroscopic devices. Detection of anemia by technicians was similar between TrueHb and HemoCue (AUC 0.92 v/s 0.90, p > 0.05). Community workers performed better with Hemocue for detecting anemia compared to TrueHb (AUC 0.92 v/s 0.90, p < 0.05). For detection of severe anemia, accuracy of TrueHb was significantly better with technicians (AUC 0.91 v/s 0.70; p < 0.05) and community workers (AUC 0.91 v/s 0.73; p < 0.05). HemoCue showed a bias or mean difference (95%CI) of 0.47 g/dl (0.42, 0.52) for all values, and 0.92 g/dl (0.82, 1.03) for severe anemia. For TrueHb, it was − 0.28 g/dl (− 0.37, − 0.20) for all readings, and 0.06 g/dl (− 0.52, 0.63) for severe anemia. TrueHb appeared to be more consistent across different weather conditions, although it overestimated Hb in extreme cold weather conditions. Conclusion For detection of anemia, True Hb and HemoCue were comparable. For severe anemia, True Hb seemed to be a better and feasible point-of-care device for detecting anemia in the community settings.